Asymmetric Construction of the C(sp3)–SCF3 Motif by CuH-Catalyzed Hydrofunctionalizations of 1-SCF3-Alkenes - Kojima, Yuki; Hirano, Koji (Synlett, 2025)
Trifluoromethylthio (SCF3)-containing molecules are highly valuable in medicinal chemistry and agrochemistry, and efficient synthetic methods for their preparation have thus been developed. However, the asymmetric construction of the C(sp3)–SCF3 motif still remains largely underdeveloped. Herein, we summarize our recent work on the CuH-catalyzed hydrofunctionalizations of 1-SCF3-alkenes, which enable the asymmetric synthesis of nontrivial C(sp3)–SCF3 compounds that are difficult to prepare by other means.
Keywords: Asymmetric catalysis; Copper; Hydrofunctionalization; Organofluorine molecules; Trifluoromethylthio group